2012
DOI: 10.1007/s00234-012-1095-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 3D computer-aided with manual cerebral aneurysm measurements in different imaging modalities

Abstract: Computer-aided aneurysm measurement in 3D offers improved intra- and inter-observer reliability and a reproducible parameter extraction, which may be used in clinical routine and as objective surrogate end-points in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…The size of aneurysm is generally assumed to be the maximum diameter, but the method used to measure the maximum diameter and the imaging modality to obtain the data significantly affects the measurement. 25 To improve the precision of the prediction and the clinical pertinence and usability, the assessment of the criteria needs to be improved and refined.…”
Section: Limitations Because Of Variable Measurement Lack Of Precisionmentioning
confidence: 99%
“…The size of aneurysm is generally assumed to be the maximum diameter, but the method used to measure the maximum diameter and the imaging modality to obtain the data significantly affects the measurement. 25 To improve the precision of the prediction and the clinical pertinence and usability, the assessment of the criteria needs to be improved and refined.…”
Section: Limitations Because Of Variable Measurement Lack Of Precisionmentioning
confidence: 99%
“…Manual post-processing is time consuming and prone to error especially in the context of complex aneurysm shapes, which can be difficult to understand when presented in 2-dimensions. Specifically, it was shown that computer-aided segmentation significantly improves the otherwise limited intra- and inter-observer agreement of manual post-processing[13]. We therefore developed a software tool for the semi-automatic segmentation of cerebral aneurysms from the 4DCTA data.…”
Section: Introductionmentioning
confidence: 99%
“…Another drawback of our study is the missing correlation with conventional angiography. However, the validity of the methods of semi-automatic volumetry and image registration has been shown in previous studies [10]. The use of MRA resembles the standard of care in many centers worldwide…”
Section: Discussionmentioning
confidence: 99%
“…Within this context, it was proposed to continuously quantify aneurysm recurrence volumes by applying a rigid registration and subsequent subtraction of vessel segmentations of consecutive 3-dimensional (3D) time-of-flight magnetic resonance (MR) angiography (TOF-MRA) datasets instead of visually assessing the dichotomous end point of a recurrence development [9,10]. Although a preliminary proof-of-concept lead to promising results in terms of a possible significant reduction of sample sizes required for the evaluation of new coils [9], a study comparing different coil types is still missing.…”
Section: Introductionmentioning
confidence: 99%